A DETAILED LEGACY OF BUDDHISM IN JAMMU AND KASHMIR - Aqib Yousuf Rather (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Both the Nilamata Purana and Kalhana's Rajatarangini show the significance of Buddhism in classical Kashmiri culture. According to Buddhist history, Buddhism was introduced to Kashmir by a Varanasi monk named Majjhantika, a student of Ananda. During his administration of Srinagar in the 13th and 14th centuries, Mauryan ruler Ashoka introduced Buddhism to Kashmir. The Kushans, who ruled across Pakistan and Afghanistan in the first century, are supposed to have dominated this region. So far, there hasn't been much of a distinction in the history of Buddhism in Kashmir and the rest of the country. Before the arrival of the Aryans, the valley was inhabited by Naga, Pishacha, and Yakshas. Nagas, for example, are revered for their historical and cultural value. Both the proponent of Sankhya Darshana, Kapil, and the author of Patanjali are thought to be local Nagans. Two of the most famous Buddhist philosophers and intellectuals, Nagarjun and Naga Budhi, are also supposed to be Nagas. Following the entrance of the Aryans, these Kashmiri aborigines appear to have converted to the Vedic faith and eventually to Buddhism. The teachings of Buddhism have tremendously improved India's mentality, culture, religion, and civilization. The aim of the study is to explain the foundation and culture of Buddhism in Jammu and Kashmir.